The role of consumer behavior and power structures in coping with shoddy goods. (November 2021) - Hu, Shu; Fu, Ke; Wu, Tong
Abstract: This paper aims to understand the increasingly prevalent phenomenon of shoddy goods and help honest firms better cope with the unfair competition posed by shoddy goods producers. We develop a game-theoretic model to examine the interaction between an honest manufacturer of quality goods (the truth-teller ) and an unscrupulous producer of shoddy goods (the deceiver ). Three power structures are considered: with the truth-teller as leader, with the deceiver as leader, and with equal-power players. Our equilibrium analysis suggests that when consumers make only one-time purchase, the truth-teller is prone to suffer profit loss. Yet some power structures may help the truth-teller mitigate the risk of losing profit. Specifically, when the announced quality of the deceiver is low enough, the truth-teller-as-leader power structure reduces the truth-teller's risk of profit loss; in contrast, when the announced quality of the deceiver is not low enough, the deceiver-as-leader power structure has a better mitigating effect; and the equal-power-player power structure always works worst. We also investigate the role of consumer repurchase behavior in fighting shoddy goods by extending the model to incorporate consumer dissatisfaction and repurchase frequency. A numerical study indicates that consumers' quality expectation disconfirmation sensitivity can deter the deceiver from exaggerating its product quality – either when consumers' repurchase frequency is high or when consumers repurchase at a medium frequency in a market led by the truth-teller. Our findings yield new theoretical insights for firms and industries seeking to combat shoddy goods. Highlights: We enrich the current literature on low-quality goods to consider shoddy goods. We analyze the game between truth-tellers and deceivers in three power structures. We investigate the role of consumer repurchase behavior in fighting shoddy goods. We provide guidance on fighting unfair competition posed by shoddy goods producers.